A RESEARCH ON HR PRACTICES INFLUENCING ORGANISATIONAL COMMITMENT LEADING TO RETENTION BASED ON EXPERIENCE - Kumarasamy, Dr. P.; Palani, Dr. A. (International Journal of Psychosocial Rehabilitation, 2020)
A high degree of organisational loyalty is characterized by a deep appreciation of the ideals of the organisation and a desire to continue to work for the organisation. It is seen that high organisational commitment means identifying with the organisation employed. The willing to remain suggests that behavioural tendencies at this level are closely related to the affective dimension of commitment, where people stay because they want to. The objectives of this study are to identify the HR Practices influencing organisational commitment among bank managers of private banks in Chennai, understand the extent to which organisational commitment helps in retaining bank managers and investigate the association between experience of bank managers and their commitment towards work leading to employee retention. This study would also help employers to understand the ignored trivial needs of the employee. It would also help in understanding whether the focus of the employee is on job related practices or personal related practices from his own perspective and the perspective of family and wellbeing.